Unraveling the Frontiers of Nanomedicine: Exploring Advancements and Envisioning the Future - Shivam Rongpi,; Islam, Injamul; Ananta Choudhury,; Charlisar Teron, (Asian Journal of Pharmaceutical Research and Development, 2024)
Nanomedicine is an emerging field at the junction of nanotechnology and medicine that provides high-order therapeutic solutions for different diseases. This review discusses the latest developments and future directions in nanomedicine applications in diverse areas of drug delivery, diagnostics, and tissue regeneration.Nanoparticles are engineered at the nanoscale level and, hence, play a very significant role in targeted drug delivery, improving the efficacy of drugs with reduced side effects. This has resulted in recent developments that include the functionalization of nanoparticles that can attach precisely to specific cells or tissues and stimuli-responsive nanoparticles for the controlled release of drugs depending upon environmental triggers.Nanoparticles also revolutionize medical imaging and diagnostics by acting as contrast reagents and sensitive and accurate imaging methods. In this context, SPIONs enhance magnetic resonance imaging, while gold nanoparticles improve optical imaging modalities due to their unique properties.NPs have been proven to be very useful for therapeutic applications, including cancer therapy, gene therapy, and regenerative medicine. Moreover, liposomes and polymer-based nanoparticles can deliver target drugs, lowering systemic toxicity at the tumor site. MSNPs ferry growth factors for tissue repair or act as scaffolds for cell transplantation.Compared to all of the possible benefits of nanomedicine, ensuring the safety and nontoxicity of nanoparticles overwhelmingly comes first. Researchers are working on analyses of the long-term interactions between nanoparticles and biological systems and developing appropriate regulatory frameworks that will enable the safe and responsible use of these materials.The potential for nanomedicine to create opportunities in personalized medicine, combined therapies, and "smart" treatments is considerable. However, to come up with that kind of future vision, enormous challenges lie in the pathway forward—which especially includes regulatory approval and the creation of scalable pathways for manufacturing.